Enhanced electrocatalytic activity of nitrogen-doped multi-walled carbon nanotubes towards the oxygen reduction reaction in alkaline media. Issue 73 (9th August 2015) - Vikkisk, Merilin; Kruusenberg, Ivar; Ratso, Sander; Joost, Urmas; Shulga, Eugene; Kink, Ilmar; Rauwel, Protima; Tammeveski, Kaido
<x xml:space="preserve">Abstract</x> Nitrogen-doped carbon nanotube materials derived from dicyandiamide and cyanamide are highly active electrocatalysts for oxygen reduction reaction in alkaline media.